A rare cause of chest pain mimicking myocardial infarction - Kudret Keskin; Murat Başkurt; Faruk Aktürk; Cenk Conbayır (KARE Publishing, 2014)
e present a patient who underwent endoscopic retrograde cholangiopancreatography procedure for bile duct stone removal and sphincterotomy. Upon completion of the procedure, the patient experienced severe chest pain. Because myocardial infarction was the likely diagnosis, we immediately performed a coronary angiography, which identified severe coronary lesions without any total occlusion. Being skeptical of the possible cause, we searched for alternative causes and interestingly found pneumothorax, pneumomediastinum, and retro-intra-abdominal free air. This rare complication is particularly important for a cardiologist because they should be aware of such a complication, and correlation with the symptoms and coronary lesions should always be made.